2019
DOI: 10.1002/ange.201903290
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Plasmonic and Electrocatalytic Activation of Methanol Oxidation on Palladium–Silver Alloy Nanotubes

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…By separating and directing them to the surface of catalysts, light illumination‐induced hot charge carriers can be coupled to various chemical/electrochemical reactions and accelerate the reaction rates. [ 181–183 ] In addition, sunlight is an environmentally friendly and inexhaustible resource in nature. Therefore, harvesting optical energy by grafting photosensitive materials onto catalysts represents a promising route to promote electrocatalytic HER/OER activity.…”
Section: Light‐assisted Electrocatalytic Her/oermentioning
confidence: 99%
“…By separating and directing them to the surface of catalysts, light illumination‐induced hot charge carriers can be coupled to various chemical/electrochemical reactions and accelerate the reaction rates. [ 181–183 ] In addition, sunlight is an environmentally friendly and inexhaustible resource in nature. Therefore, harvesting optical energy by grafting photosensitive materials onto catalysts represents a promising route to promote electrocatalytic HER/OER activity.…”
Section: Light‐assisted Electrocatalytic Her/oermentioning
confidence: 99%
“…Finally, the Au nanobipyramid/end Pd showed significantly higher photocatalytic activity, which agrees well with what is expected from their high local electric field enhancement. [ 245 ] In addition, noble‐metal composites with unique structures have also been successfully applied for various electrocatalytic reactions, such as the oxygen evolution reaction (OER), [ 246–248 ] ORR, [ 249,250 ] HER, [ 251,252 ] MOR, [ 253 ] and formic acid oxidation. [ 254 ] Ye and co‐workers assembled plasmonic Au nanoparticles on Ni(OH) 2 nanosheets.…”
Section: Applicationsmentioning
confidence: 99%
“…Some researchers revealed that the hot holes act as strong oxidants to drive the electrons transfer from adsorbed molecules to the plasmonic nanoparticles. [170,171] Some works demonstrated that the plasmonic effects can lead to surface charge heterogeneity which results in decreasing d-band centre of Pt and thereby leads to inhibit the adsorption of poisoning species. [164,172,173] Therefore, profound and holistic investigations are still deeply required to precisely understand the mechanism or the contributions of each component, which can be extraordinarily helpful to develop high-efficiency AOR catalysts.…”
Section: Assisted From Other Energiesmentioning
confidence: 99%
“…However, the real underlying mechanism of plasmon‐enhanced electrocatalytic reactions remains highly controversial. Some researchers revealed that the hot holes act as strong oxidants to drive the electrons transfer from adsorbed molecules to the plasmonic nanoparticles [170,171] . Some works demonstrated that the plasmonic effects can lead to surface charge heterogeneity which results in decreasing d‐band centre of Pt and thereby leads to inhibit the adsorption of poisoning species [164,172,173] .…”
Section: Advanced Strategies For High‐performance Aor Electrocatalystsmentioning
confidence: 99%